Vacuum system design, construction, and operation for the Cornell High Energy Synchrotron Source upgrade. (April 2021) - Lushtak, Yevgeniy; Burke, David; Li, Yulin; Lyndaker, Aaron; Liu, Xianghong; Ying, Laurel
Abstract: During the summer and fall 2018, the Cornell High Energy Synchrotron Source (CHESS), underwent an upgrade that recast the facility as primarily a low emittance X-ray source. The upgrade replaced one sixth of the Cornell Electron Storage Ring (CESR) with six double-bend achromats, featuring four novel CHESS Compact Undulator (CCU) insertion devices, and switched CESR to single particle beam operation. At the time of this writing, the upgraded storage ring has achieved the CHESS-U design goal of operating with 200 mA of positron current at 6.0 GeV beam energy. Seven out of eleven CHESS-U beamlines are currently in X-ray user operation. The construction and the commissioning of the new section of the CESR accelerator required novel solutions to design, fabrication, and vacuum system operations. Significant design considerations and efforts were made to minimize X-ray 'dark-time', returning to operation less than 1 year. This paper describes the important milestones of the process, the solutions implemented, and the present status of CHESS-U. Highlights: The Cornell High Energy Synchrotron Source has been upgraded for low-emission operation. The upgrade relies heavily on stretch-formed aluminum extrusions. High capacity non-evaporable getter pumps dominate the pumping scheme. A novel vacuum simulation approach was developed to track pump status.